Muslim Motherhood - Ahmed, Sofia (Journal of the Motherhood Initiative for Research and Community Involvement, 2024)
This article explores the complexities and intersections of cultural, religious, and socioeconomic factors that shape Muslim motherhood and the resiliency of Muslim mothers while raising children in North America. I argue that Muslim mothers are marginalized in an intersectional manner. As Muslims, they are religious minority group members in the West, and the majority are members of racialized minority groups of colour. The concept of “killjoy” is explored as a means of representing the heaviness of maternal guilt felt by Muslim mothers raising resilient children in the West. I share my mothering journey and new perspectives on being a killjoy.